Uniportal video assisted thoracoscopic lobectomy: primary experience from an Eastern center - Feng, Mingxiang; Shen, Yaxing; Wang, Hao; Tan, Lijie; Mao, Xuping; Liu, Yi; Wang, Qun (Journal of Thoracic Disease; Vol 6, No 12 (December 31, 2014): Journal of Thoracic Disease, 2014)
Background: Uniportal video-assisted thoracoscopic surgery (VATS) lobectomy is an emerging technique for the surgical resection of non-small cell lung cancer (NSCLC). Besides its wide debates on safety and efficacy throughout the world, there were few report on uniportal VATS from the Eastern countries. In this article, we summarized our primary experience on uniportal VATS lobectomy in an Eastern center. Methods: From October 2013 till February 2014, 54 consecutive uniportal VATS lobectomy were performed in the Department of Thoracic Surgery, Zhongshan Hospital of Fudan University. Patients’ clinical features and operative details were recorded. Post-operatively, the morbidity and mortality were recorded to analyze the safety and efficacy of uniportal VATS lobectomy for NSCLCs. Results: Among the 54 planned uniportal VATS lobectomy, there was one conversion to mini-thoracotomy due to lymph node sticking. Extra ports were required in two patients. The uniportal VATS lobectomy was achieved in 51 out of 54 patients (94.4%). The average operation duration was 122.2±37.5 min (90-160 min).The average volume of estimated blood loss during the operation was 88.8±47.1 mL (50-200 mL). The mean chest tube duration and hospital stay were 3.2±1.9 days and 4.6±2.0 days, respectively. There was no postoperative mortality in this study. Two patients suffered from prolonged air leakage (5 and 7 days), and one atrial fibrillation was observed in this cohort. Conclusions: Based on our primary experience, uniportal VATS lobectomy is a safe and effective procedure for the surgical resection of NSCLCs. The surgical refinements and instrumental improvements would facilitate the technique. Further studies based on larger population are required to determine its benefits towards patients with NSCLCs.